DEVICE FOR MONITORING AND PREVENTION OF INJURIES DURING PHYSICAL ACTIVITY USING A SMART BRACELET AND WATCH - Alvarez-Abarca, Erica; Casos-Mamani, Hector; Maldonado-Aguilar, Adrian; Esquicha-Larico, Elias; Cardenas-Gutierrez, Victor; Cuya-Zevallos, Carla; Mamani Machaca, Elizabeth Susan (LACCEI, 2025)
The monitoring of physical activity through wearable devices has significantly advanced, mainly focusing on basic parameters such as heart rate and calories burned. However, these devices often lack the capability to assess the correct execution of movements, a critical factor in preventing sports injuries. Existing patents and technologies, including optical sensors in smart glasses, gesture-controlled smartwatches, and electromyographic armbands, demonstrate progress in detecting physiological parameters and body movements but have limitations in active injury prevention. Therefore, integrating motion and heart rate sensors to identify and alert users about harmful movements during physical activity presents an innovative opportunity to enhance the safety and effectiveness of sports training.